Filsafat Penerimaan Dalam Kesehatan Mental: Nrimo ing Pandum sebagai Mekanisme Coping di Era Modern: Philosophy of Acceptance in Mental Health: Accepting Acceptance as a Coping Mechanism in the Modern Era - Rahman, Muchamad Salamun Abdul; Kuswanjono, Arqom (Jurnal Filsafat Indonesia, 2025)
Modernization is like a knife edge, on the one hand, through advances in science and technology, It offers acceleration in all aspects of life which ultimately makes various matters easier and it definitely creates advances human civilization. Human increasingly feel isolated and leaves an empty space in their soul, it brings distress, depression and full of pressure through the ambition to always be the best, it also brings exposure to hoaxes, high crime rates, especially cyber crime, and many other stressors that arise because of all of those acceleration. This research aims to examine the Javanese philosophy of nrimo ing pandum as an alternative coping strategy amidst the onslaught of modernization. Nrimo culture means sincerely accepting all life's challenges that occur after trying to get through them. As for the results, it is left to God's will alone. Researchers used the narrative review method which was carried out on ten articles about nrimo ing pandum from 2018-2024 and obtained from Google Scholar and PubMed. The results of the research explain the genealogy/cultural history of nrimo ing pandum and how the mechanisms of nrimo philosophy can be beneficial for a person's mental health.